Research on the Thinking and Creativity of the Future Teacher in the Global Process, as Well as Preparation for an Innovative Lesson - Shadiev Fakhriddin Teshaevich (International Journal on Integrated Education, 2022)
The article discusses the issues of training innovative and creative modern future primary school teachers in the spirit of high spirituality and patriotism, the formation of technology of competitive tasks and responsibilities of young professionals in the global process, and improving the education system to international standards.